The last human : a guide to twenty-two species of extinct humans - Sarmiento, Esteban E.; Sawyer, G. J. (Gary J.); Milner, Richard, 1941-; Deak, Viktor; Tattersall, Ian. (New Haven, Conn. : Yale University Press, 2007)
Creates three-dimensional scientific reconstructions for twenty-two species of extinct humans, providing information for each one on its emergence, chronology, geographic range, classification, physiology, environment, habitat, cultural achievements, coexisting species, and possible reasons for extinction.
Appendix 2. Portraits of prehistory : imaging our ancestors / by Richard Milner.
"A Peter N. Nevraumont book."
Includes bibliographical references (p. 251) and index.
Keywords: Fossil hominids; Human evolution; Paleoanthropology -- Methodology; Human beings -- Origin